2017
DOI: 10.1590/s0102-865020170040000008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epidurally administered dexamethasone with lignocaine for post-operative analgesia in dogs undergoing ovariohysterectomy. A dose-response study

Abstract: Purpose: To evaluate the postoperative analgesic and adverse effects of three doses of dexamethasone, administered epidurally in combination with lignocaine, in dogs undergoing ovariohysterectomy (OVH). Methods: Twenty-four female dogs undergoing ovariohysterectomy were pre-medicated with acepromazine and general anaesthesia was induced and maintained with propofol. Animals were randomly allocated into four groups of six. The control group was given lignocaine 2% (LI) and the treatment groups were given lignoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…While evaluating the use of lidocaine through epidural administration, previous studies (DeRossi et al, 2016) also observed that the animals that received only lidocaine required rescue analgesia after two hours in the postoperative period. These results are similar in female dogs subjected to ovariohysterectomy that received only lumbosacral epidural lidocaine (Hermeto et al, 2017).…”
Section: Discussionsupporting
confidence: 63%
“…While evaluating the use of lidocaine through epidural administration, previous studies (DeRossi et al, 2016) also observed that the animals that received only lidocaine required rescue analgesia after two hours in the postoperative period. These results are similar in female dogs subjected to ovariohysterectomy that received only lumbosacral epidural lidocaine (Hermeto et al, 2017).…”
Section: Discussionsupporting
confidence: 63%
“…The anesthetist used 22G-gauge Touhy-type epidural needles. The method was confirmed using the loss resistance technique (Valverde 2008;Hermeto et al 2017). Dogs were randomly assigned to three experimental groups: the lidocaine -control-group (GL, n = 7) medicated with 2 mg Kg -1 ; the lidocaine-fentanyl group (GLF, n = 7) that received the same dose of lidocaine in combination with 3 µg Kg -1 of fentanyl; and the lidocaine-morphine group (GLM, n = 7) that received the same dose of lidocaine plus morphine at 0.1 mg Kg -1 .…”
Section: Experimental Designmentioning
confidence: 99%
“…The technique chosen in this study was based on the data observed in humans 12 and also on the difficulty of the tutor in adhering to the conservative treatment with oral anti-inflammatory because it is a herding dog whose dwelling in a rural area would interfere with the administration of the drug. Thus, electro stimulation-guided epidural administration combining dexamethasone (4mg) 13 , bupivacaine 0.125% (0.22mL. kg -1 ), and morphine (0.1mg.kg -1 ) 14 was the selected approach.…”
Section: Case Reportmentioning
confidence: 99%
“…Dexamethasone has been frequently used in analgesic blockades with the main advantage being its high potency and duration. In veterinary medicine, only one study reports the use of epidural dexamethasone 13 . This work evaluated the analgesic influence of different doses of dexamethasone (2, 4 and 8 mg) associated with lidocaine in dogs submitted to ovary salpingohisterectomy.…”
Section: 7mentioning
confidence: 99%